2011
DOI: 10.9758/cpn.2011.9.3.134
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole Improved Obsessive Compulsive Symptoms in Asperger's Disorder

Abstract: There are many comorbid disorders associated with autism spectrum disorders in child and adolescent population. Although obsessive compulsive disorder and autism spectrum disorders (ASD) comorbidity has common in clinical practice, there are few reports about psychopharmacological treatment for obsessive compulsive symptoms in children with ASD in the literacy. We report a successful treatment case with aripiprazole in Asperger's Disorder with obsessive compulsive symptoms. The Yale Brown Obsessive Compulsive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…These studies had not examined the effect of aripiprazole on irritability in autism. The other reasons for exclusion were as follows: not a clinical trial 10 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 , not double blind trials 37 39 40 41 42 , post-hoc analyses 43 44 45 , no control group 46 , case reports 47 48 49 50 51 52 53 54 55 , switching risperidone to aripiprazole 56 57 , data re-analysis 58 , assessed body mass index changes 59 , prevention of irritability 60 , and retrospective studies 61 62 63 64 65 . One study reported anti-manic effect of aripiprazole in patients with autism spectrum disorder and bipolar disorder 66 .…”
Section: Resultsmentioning
confidence: 99%
“…These studies had not examined the effect of aripiprazole on irritability in autism. The other reasons for exclusion were as follows: not a clinical trial 10 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 , not double blind trials 37 39 40 41 42 , post-hoc analyses 43 44 45 , no control group 46 , case reports 47 48 49 50 51 52 53 54 55 , switching risperidone to aripiprazole 56 57 , data re-analysis 58 , assessed body mass index changes 59 , prevention of irritability 60 , and retrospective studies 61 62 63 64 65 . One study reported anti-manic effect of aripiprazole in patients with autism spectrum disorder and bipolar disorder 66 .…”
Section: Resultsmentioning
confidence: 99%
“…The search yielded 9 case reports reporting OCD in ASD with psychopharmacological management [11][12][13][14][15][16][17][18][19]. In the 9 cases that were included in this review, the mean age of the patients was 14.4 ± 3 years old and 77.78% (7/9) were male.…”
Section: Clinical Cases In Literaturementioning
confidence: 99%
“…The concerned position argues that the number of patients taking medication could be inflated, since separate disorders are combined into a single disorder. Also, since the new category is a re-organization based on symptoms, not a categorization based on etiological or biological evidence, conservative treatment would still continue 6). However, there could be positive effects in matters such as applying and assessing therapeutic effects since assessment could be done by a single standard.…”
Section: Introductionmentioning
confidence: 99%
“…Also, since the new category is a re-organization based on symptoms, not a categorization based on etiological or biological evidence, conservative treatment would still continue. 6) However, there could be positive effects in matters such as applying and assessing therapeutic effects since assessment could be done by a single standard. In other words, results from previous studies on five separately diagnosed patients or disorders may prove difficult to interpret and combine while a single diagnostic approach to similar developmental disorders simplifies the investigation of etiology and pathogenesis.…”
Section: Introductionmentioning
confidence: 99%